DURABILITY OF THE MEDIA UNDER EU LAW AND LITHUANIAN LAW - Drazdauskas, Stasys (Teisė, 2015)
In recent decades, there was an increase in formalism in contract law, where additional requirements for form of agreement or for information provided were introduced, especially in the area of consumer law. Therefore, analysis of such new legal requirements, their trends, and application practice becomes relevant. Historical analysis of legislature confirms that “durable medium” requirement was established in EU law in order to ensure that consumers remain able to rely in the future on the information received via instantaneous electronic communication technologies. The primary and only element and requirement of “durable medium” was persistency (durability) of the information. In later legislative initiatives “durable medium” definition was changed by supplementing it with example list of media; however, such casuistic approach turned out to be in contrast to the changing technological environment. Therefore, the newest legal sources rightly do not contain such lists any more. The case law interprets “durable medium” too formalistically and by introducing such additional safety requirements, which were not foreseen in the legal instruments and were not intended by the legislator.